Synopsis of Begonia (Begoniaceae) of southwest Sulawesi and the Selayar Islands, Indonesia, including one new species - Thomas, Daniel C.; Ardi, Wisnu H. (Phytotaxa, 2020)
The diversity of the Begonia flora of the southwestern arm of Sulawesi and the adjacent Selayar Islands, South Sulawesi province, Indonesia, is reassessed, and distribution maps, provisional IUCN conservation category assessments, and an identification key to 14 recognised species are provided. One new species from the Selayar Islands, Begonia enoplocampa, is described and a photo plate is presented. This species is the first record of Begonia section Jackia in South Sulawesi province. Newly available material allowed a reassessment of the morphological variability of several species that were originally described from very limited material. Resulting revised descriptions and photo plates of Begonia comestibilis, B. hooveriana, B. ozotothrix, B. prionota and B. siccacaudata are presented. Begonia hooveriana is lectotypified.